Strength and toughness in shear of constrained layers. (1st May 2018) - Biel, Anders; Stigh, Ulf
Abstract: Confined layers may fracture in shear. This occurs, for example in adhesive joints and composite materials. A common mechanism for shear fracture is the formation of shear hackles associated with an expansion of the layer. This makes shear toughness and strength depend on the constraint of the expansion. By constraining the expansion using external loading in experiments, the expansion is reduced but not totally inhibited. The experiments are evaluated using the path independent properties of the J -integral. It is shown that the shear toughness increases for the more constrained case. Thus, from a strength analysis perspective, ignoring the expansion leads to a conservative estimate of the fracture properties. Extrapolation of the evaluated properties to totally inhibited expansions gives the traction separation relation and the fracture toughness for a layer in simple shear.